Asian Trade Flows: Trends, Patterns, and Projections - Prema-chandra Athukorala (Asian Development Bank (ADB), 2011)
This paper provides trade flow projections for major Asian developing economies (ADEs) up to 2030 against the backdrop of an in-depth analysis of policy shifts and trade patterns over the past 4 decades. Merchandise trade of ADEs has grown at a much faster rate in the global context, with a distinct intraregional bias. Global production sharing has become a unique feature of the economic landscape of the region, with the People's Republic of China playing a pivotal complementary role as the premier assembly center within the regional production networks. According to the projections made within the standard gravity modelling framework, total real nonoil trade of ADEs would increase at an average annual rate of 8.2 during the next 2 decades, with a notable convergence of individual countries' rates to the regional average. The share of intraregional trade in total nonoil trade would increase steadily from 53% in 2010 to 58% in 2030. The trade-to-GDP ratio would increase from 39.4% and 74.4% between these 2 years. These predictions need to be treated with caution as they are based on the assumption that the trade structure pertaining to the estimation period will remain unchanged in the next 2 decades.
hdl:11540/2057
Keywords: 330; Internationale Wirtschaft; Internationale Wirtschaftsbeziehungen; Außenhandelsstruktur; Außenwirtschaftspolitik; Handelseffekt; Asien